2022
DOI: 10.1007/s00248-022-02023-7
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Analysis Reveals a New Microsporidia-Host Association in a Freshwater Lake

Abstract: Microsporidia are a large group of obligate intracellular eukaryotic parasites. Recent studies suggest that their diversity can be huge in freshwater lake ecosystems especially in the <150 µm size fraction. However, little is known about their hosts and therefore their impact on the trophic food web functioning. In this study, single cell analysis and fluorescence microscopy were used to detect new host-parasite association within rotifer communities in lake Aydat (France). Our analysis showed the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Using TSA‐FISH with a universal microsporidian probe (USP01; Chauvet et al 2022 a ) we confirmed the Microsporidia‐ Kellicottia (rotifer) association already observed in another lake (Chauvet et al 2022 a , b ), here in lake Chauvet. We also identified microsporidian infections in dinoflagellates (probably belonging the genus Ceratium ) both in freshwater and marine ecosystems (Fig.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Using TSA‐FISH with a universal microsporidian probe (USP01; Chauvet et al 2022 a ) we confirmed the Microsporidia‐ Kellicottia (rotifer) association already observed in another lake (Chauvet et al 2022 a , b ), here in lake Chauvet. We also identified microsporidian infections in dinoflagellates (probably belonging the genus Ceratium ) both in freshwater and marine ecosystems (Fig.…”
Section: Resultssupporting
confidence: 84%
“…In this genus, only one species is described ( Crispospora chironomi ) and known to parasite chironomid larvae ( Chironomus plumosus ) in freshwater ecosystems (Tokarev et al 2010). Moreover, a recent study suggests that a new Crispospora species might be able to parasitize Kellicottia rotifers in lake environments (Chauvet et al 2022 b ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations